Two stages of economic development - Gang Gong (Asian Development Bank Institute (ADBI), 2016)
This study suggests that the development process of a less-developed country can be divided into two stages, which demonstrate significantly different properties in areas such as structural endowments, production modes, income distribution, and the forces that drive economic growth. The two stages of economic development have been indicated in the growth theory of macroeconomics and in the various "turning point" theories in development economics, including Lewis's dual economy theory, Kuznets curve, and the middle-income trap. A dynamic macroeconomic model is constructed to simulate the development process that reveals these two stages. Using the two-stage theory of economic development, we find that the People's Republic of China's economy is currently at the intersection between the first and second stages. This is the definition of "new normal" in the current Chinese economy.
Keywords: O11; E10; C61; C62; 330; dual economy theory; Kuznets curve; economic growth; new normal